The Bending-Gradient theory for flexural wave propagation in composite plates. (15th May 2020) - Bejjani, Nadine; Margerit, Pierre; Sab, Karam; Bodgi, Joanna; Lebée, Arthur
Abstract: This paper is concerned with the prediction of the propagation of flexural waves in anisotropic laminated plates with relatively high slenderness ratios by means of refined plate models. The study is conducted using the Bending-Gradient theory which is considered as an extension of the Reissner–Mindlin theory to multilayered plates. Two projections of the Bending-Gradient model on Reissner–Mindlin models are also explored. The relevance of the proposed models is tested by comparing them to well-known plate theories and to reference results obtained using the finite element method.